2007
DOI: 10.1186/1471-2148-7-50
|View full text |Cite
|
Sign up to set email alerts
|

Spatial mosaic evolution of snail defensive traits

Abstract: Background: Recent models suggest that escalating reciprocal selection among antagonistically interacting species is predicted to occur in areas of higher resource productivity. In a putatively coevolved interaction between a freshwater snail (Mexipyrgus churinceanus) and a molluscivorous cichlid (Herichthys minckleyi), we examined three components of this interaction: 1) spatial variation in two putative defensive traits, crushing resistance and shell pigmentation; 2) whether abiotic variables or frequency of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(37 citation statements)
references
References 26 publications
3
34
0
Order By: Relevance
“…Shell plasticity in mollusks remains heavily studied since shell phenotypes are readily measured and driven by a combination of genetic and environmental factors (e.g., Hoverman & Relyea, 2007;Johnson et al, 2007;Preston & Roberts, 2007). Though authors had previously described the relationship of shell inflation and sculpture to freshwater environments (see previous references and review in Ball, 1922), Ortmann also noted that, while he had confirmed a similar relationship in the pleurocerid genus Io as described by Adams (1915), relatively few freshwater mussel or snail species had been observed showing this pattern of morphological variation.…”
Section: Discussionmentioning
confidence: 99%
“…Shell plasticity in mollusks remains heavily studied since shell phenotypes are readily measured and driven by a combination of genetic and environmental factors (e.g., Hoverman & Relyea, 2007;Johnson et al, 2007;Preston & Roberts, 2007). Though authors had previously described the relationship of shell inflation and sculpture to freshwater environments (see previous references and review in Ball, 1922), Ortmann also noted that, while he had confirmed a similar relationship in the pleurocerid genus Io as described by Adams (1915), relatively few freshwater mussel or snail species had been observed showing this pattern of morphological variation.…”
Section: Discussionmentioning
confidence: 99%
“…2007). To generate the level of mitochondrial introgression in a population, we combined new mitochondrial haplotype sequences ( n  =   82) with published data for CYTB ( n  =   180) from Hulsey and García de León (2013).…”
Section: Methodsmentioning
confidence: 99%
“…2007). The mtDNA haplotypes were taken from two studies ( 3 Hulsey and García de León 2013; 4 this study).…”
Section: Methodsmentioning
confidence: 99%
“…As discussed below, previous studies have demonstrated that various top-down predatory influences have a major effect on gastropod avoidance and foraging behavior (Corr et al, 1984;Alexander & Covich, 1991a, b;Dalesman et al, 2007Dalesman et al, , 2009aWojdak, 2009), life history (Crowl, 1990;Crowl & Covich, 1990;Crowl & Schnell, 1990), and shell morphology (Vermeij & Covich, 1978;DeWitt, 1998, DeWitt et al, 1999, Krist, 2002, Johnson et al, 2007. All these predator-prey interactions can alter competitive outcomes among different gastropod species.…”
Section: Introductionmentioning
confidence: 93%
“…Examples include burrowing into sediments, Herichthys minckleyi papilliforms (right D) exhibit gill arches modified into more gracile pharyngeal jaws with small muscles and pointed teeth that are ineffective at crushing snails while H. minckleyi molariforms (left D) have robust muscles and enlarged crushing teeth on their pharyngeal jaws that seem clearly modified to crush snails. E portrays heterogeneity in habitats with Nymphaea (top) and without Nymphaea (bottom) (from Johnson et al, 2007) shaking to escape from a predator's grasp, movement to close refugia (crevices, under rocks), as well as crawling into deeper waters or passively dispersing to other more distant habitats by floating (catastrophic drift). Life-history traits such high dispersal, fecundity, delayed age at first reproduction to increase growth rates provide highly flexible responses that can diminish the risk of predation (e.g., Crowl & Covich, 1990;DeWitt, 1998;Chase, 1999;Lewis, 2001;Krist, 2002;Turner, 2008).…”
Section: Behavioral Traitsmentioning
confidence: 99%